Empowering Local Governance through Data-Driven Capacity Building: Assessing Computer Literacy and Data Utilization - Yumen, Nolan M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
In the era of digitalization and data-driven governance, local government units (LGUs) face growing pressure to enhance their computer literacy and data utilization skills. This study provides a focused assessment of these critical competencies within Antique Province, Philippines, an agricultural region striving to bridge the digital divide, the gap between those with access to modern information technologies and those without. Using a mixed-methods approach, which includes surveys, interviews, focus group discussions, and secondary data analysis, the research evaluates the digital capabilities and data-driven governance practices among LGUs. The findings reveal notable disparities in computer literacy and data usage, with some LGUs making progress in digital transformation while others face challenges such as infrastructure limitations, resource constraints, and skills gaps. This study also identifies innovative strategies and best practices from successful LGUs that could serve as models for others. The research proposes specific recommendations to address these gaps, such as establishing training programs, investing in digital infrastructure, and fostering strategic partnerships. Additionally, it emphasizes the need for change management, a data governance policy framework, and a culture of continuous learning to ensure sustainable progress. By addressing these barriers, this study aims to empower Antique Province LGUs, enhancing decision-making, resource allocation, and overall service delivery through data-driven capacity building.